Pendidikan Anak di Zaman Modern: Upaya Menghadapi Perkembangan Teknologi: Childhood Education in Modern Times: Coping with Technological Developments - Riyadh Maulidi, Ahmad; Shalilah, Auladina (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2021)
The appear of technology today has changed the technicality of education in general. Technology is the main characteristic for the development of education in modern times. The presence of this technology does not only produce a positive impact. It turns out that the negative impact caused by technology is far greater in effect on the failure of education itself. So it is necessary to inculcate the principle of rejecting harm rather than taking advantage. This is interesting for researchers to formulate how the ideal education concept in modern times with this mudarat rejection approach. This research method uses a qualitative descriptive method with a literature study approach. The material obtained from related references is then analyzed with the author's observations so far. The results of this study indicate that there are five strategies that can be applied in educating children in modern times, that is 1) always improving themselves for the child's parents, 2) looking for a good wife, 3) educating the child's ideology and intellectuality, 4) educating the child psychologically and 5) educating the child's social and ethical behavior.